Evaluation of physico-chemical and sensory properties of jam and jelly prepared from paniol (Flacourtia jangomos) fruits (Current Horticulture, 2024)
The experiment was conducted to evaluate physico-chemical and sensory properties of value-added products of paniol [Flacourtia jangomos (Lour.) Raeush] fruits, in the Laboratory, Department of Horticulture, B N College of Agriculture, Biswanath, Chariali, during 2014-2016. The factorial complete randomized design in replicate was followed. The products were stored at ambient and refrigerated conditions and analysed qualitatively at 30 days interval. The result showed that storage condition and storage duration significantly influenced the physico chemical characteristics of jam and jelly. The TSS, acidity, reducing sugar and total sugar were in increasing trend, whereas ascorbic acid and anthocyanin content were in decreasing trend with increase in storage periods. The TSS content of jam ranged from 68 to 68.70%, acidity 0.85 to 1.01%, total sugar 6.39 to 7.07%, ascorbic acid 4.85 to 3.51 mg/100g and anthocyanin content 3.50 to 1.33mg/100g. Similarly, TSS jelly ranged from 65 to 66.08%, acidity 0.85 to 1.09%, total sugar 6.78 to 7.17% ascorbic acid 4.67 to 3.46mg/100g and anthocyanin content 3.61- 1.35mg/100g. There was no significant interaction effect of storage duration and storage condition in jam and jelly during the storage period. The overall sensory score for colour, flavour and taste/texture were highest in jelly (24.40) than that of jam (21.74) at the end of storage period. Sensory evaluation results revealed that paniol jam and jelly kept under refrigerated condition remain organoleptically acceptable to consumers for 6 months.
Keywords: Physico-chemical; Sensory properties; Jam Jelly; Value-added products; Storage; Acidity; Reducing sugar